Tổng hợp perovskit LaCrO3 bằng phương pháp đốt cháy gel ở nhiệt độ thấp - Đại và cộng sự, Lưu Minh (Vietnam Journal of Chemistry, 2014)
LaCrO3 powder has been synthesised at low temperature (700oC) by the combustion of gel prepared from polyvinyl alcohol (PVA) and metal nitrates. LaCrO3 characterization is examined by X-ray diffraction (XRD), thermogravimetric and differential thermal analysis (TG-DTA), field emission scanning electron microscopy (FESEM) and BET (Brunaure-Emmet-Teller) measurements.  The obtained sample under optional preparative conditions has nano scale with relatively large specific square area ( ~14 m2/g).